POTENSI PENGEMBANGAN WISATA PULAU BUNAKEN - Juwairia Umacina; Wawan Nurmawan; Fabiola B. Saroinsong (Universitas Sam Ratulangi, 2018)
ABSTRACT Tourism is one source of foreign exchange of this country, in addition from oil and gas sector which are very potential and has a big contribution to build the economic.This research was conducting in Bunaken island, the purpose of this research to find out the potential and obstacles of those related to tourism development of Bunaken Island. In developing tourism in Bunaken Island, the first, it need to identify the potential and obstacles in plans and structures of tourism development, so that existing potential can develop and existing obstacles can overcome. The research method was using interviews with visitors as many as 20 respondents and take the secondary data in ministry of forestry books. Furthermore, the existing data was comparing with observations / observations in the field and interviews with community leaders and managers of Bunaken, National Park. Bunaken Island have the potentials to develop as an alternative to underwater panoramas such as the addition of cultural attractions, mangrove roaming and nature, bird watching, coastal tourism development and culinary tourism and environmentally friendly agriculture. Tourism activities need to support by the availability of facilities and infrastructure such as clean water. Keywords : tourism, Bunaken Island, infrastructure, potency, obstacles.